Flashcard Race Game Enhances EFL Students' Reading Comprehension - Dian Rakhmawati; Fatma Yuniarti (English Journal Antartika, 2026)
Reading comprehension is one of the essential language skills that EFL learners must master because it significantly influences their academic achievement and language proficiency. Nevertheless, many students still encounter difficulties in identifying the main ideas, locating detailed information, making inferences, and understanding unfamiliar vocabulary while reading English texts. These problems are often associated with teacher-centered instructional practices that provide limited opportunities for active student engagement. This study aimed to investigate the effectiveness of the Flashcard Race Game in improving EFL students' reading comprehension. The research employed a quantitative approach using a quasi-experimental design involving two eleventh-grade classes. Data were collected through pre-tests and post-tests and analyzed using an independent samples t-test. The findings revealed that students taught through the Flashcard Race Game significantly outperformed those receiving conventional instruction. Moreover, the strategy enhanced students' motivation, classroom participation, collaborative learning, and confidence during reading activities. The study concludes that the Flashcard Race Game is an effective instructional strategy for improving EFL students' reading comprehension and creating a more interactive learning environment.